Pengaruh Media Pop Up Book berbasis Multisensori terhadap Kemampuan Bahasa Anak Usia Dini di Taman Kanak-Kanak Perwati - Indah Fadila, Annisa (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2023)
The purpose of this study was to find out whether the learning method using Multisensory-based Pop Up Book media affects the language skills of Early Childhood at Perwati Kindergarten. The method used is a quantitative research method. The sample in this study totaled 22 children, consisting of 11 children in class B1 and 11 children in class B2. Data collection techniques using structured observation. Based on the results of research data analysis conducted, it was found that the language skills of early childhood in the experimental class using multisensory-based pop up book media were higher than the control class. The pretest average of the experimental class was 11.91 and that of the control class was 10.91. Meanwhile, the average post-test for the experimental class was 18.76 and for the control class was 16.73. Based on the pre-test and post-test data, the average score for the experimental class was 6.46, while the average score for the control class was 5.9. Based on the sig (2-tailed) value is 0.02 <0.5. Thus there is a significant difference between the control class and the experimental class. So that it can be terminated Ha is accepted and H0 is rejected. With the results of the study it can be concluded that the use of multisensory-based pop up book media has an effect on early childhood language skills